Perfil epidemiológico de pacientes com hemofilia A e doenças associadas ao uso do fator VIII Recombinante - Bentes, Marcos do Nascimento (2020)
In Brazil, registered in the Ministry of Health, 12.983 patients with Hemophilia A. The diagnosis is based on clinical findings, laboratory tests and differential diagnosis. Treatment is to infuse the missing clotting factor. Reactions to the use of the factor can include, allergic manifestations, transfusion viral diseases and about 30% of patients develop alloantibodies. Preventive measures must be carried out with a view to improving health, quality of life and patient compliance with treatment and reducing exposure to a high number of doses of the factor. Objective: Characterize the epidemiological profile of patients with Hemophilia A, investigating diseases associated with the use of factor VIII and recombinant factor VIII at the Hospital Foundation of Hematology and Hemotherapy of Amazonas. Method: Epidemiological, cross-sectional, retrospective and documentary study. Inclusion criteria: Medical record of patients diagnosed with hemophilia A, filled with more than 70% of the information. CAAE: 11986918.6.0000.0009. Results: Registered with the Ministry of Health, a quantitative of 276 individuals diagnosed with Hemophilia A, in Amazonas. 164 medical records included for analysis of this study. Sociodemographic characteristics: male gender, 99,4%, prevalence of adolescents (28%) and young people (26,8%), brown race, 67,1%, incomplete elementary school, 28,6%, occupation: student, 42,7%. Clinical condition: 36,6% classified with severe hemophilia A. All with diagnoses, clinical and laboratory. The most common degree of kinship was that of brothers, 35,3%. Predominant symptoms: hemarthrosis (70 / 45,4%), pain (49 / 31,9%), edema (37 / 24%) and arthropathy (13 / 8,5%). Recombinant factor VIII, administered to 57 (34,8%) patients, while plasma factor VIII to 46 (28,0%), with doses ranging from 2000 IU to 2999 IU. Complications: arthralgia (77,4%) and hemorrhage (77,4%). Conclusions: Good quality care by health professionals helps to prevent serious complications, resulting in quality of life for the hemophiliac